STRATEGI PENANGANAN PEDAGANG KAKI LIMA DI MOJOAGUNG JOMBANG - Meriana Wahyu Nugroho (Universitas Hasyim Asy'ari, 2018)
The existence of PKL around Mojoagung Jombang fieldis considered to be the cause of traffic congestion and disturb the beauty of the city. This study aims to describe the existing area of Mojoagung jombang fieldwith the activity of street hawkers in it, as well as making the design of structuring street vendors in the field MojoagungJombang. This study uses Analytical Hierarchy Process approach, the formulation of PKL's next handling strategy described in the implementation of programs with attention to stakeholders' interests can be determined based on priority scale. The results obtained from the AHP approach, among others: criteria of spatial factors have the highest importance of importance that is with the weight of 0.359 (35.9%) and then followed by public order factor with the weight of 0.226 (22.6%), economic factor with weight 0.178 (17,8%), social factor with weight 0,148 (14,8%) and last environmental factor with weight of 0,089 (8,9%).